2005
DOI: 10.1016/j.gassur.2005.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Acute Mesenteric Ischemia Using Multidetector CT and CT Angiography in a Porcine Model

Abstract: Acute mesenteric ischemia, a frequently lethal disease, requires prompt diagnosis and intervention for favorable clinical outcomes. This goal remains elusive due, in part, to lack of a noninvasive and accurate imaging study. Traditional angiography is the diagnostic gold standard but is invasive and costly. Computed tomography (CT) is readily available and noninvasive but has shown variable success in diagnosing this disease. The faster scanning time of multidetector row CT (M.D.CT) greatly facilitates the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
0
20
2
3
Order By: Relevance
“…A pictorial essay by Wildermuth et al [110] illustrates this very clearly. In an animal experiment with pigs, it was able to be shown that CTA can effectively differentiate between open and embolically occluded branches of the superior mesenteric artery with a positive predictive value of 92 % [111]. In a further study in which CT units with 16 rows or more were used, excellent sensitivity and specificity values for the diagnosis of arterial mesenteric ischemia were able to be achieved [112].…”
Section: Arterial Occlusionmentioning
confidence: 96%
“…A pictorial essay by Wildermuth et al [110] illustrates this very clearly. In an animal experiment with pigs, it was able to be shown that CTA can effectively differentiate between open and embolically occluded branches of the superior mesenteric artery with a positive predictive value of 92 % [111]. In a further study in which CT units with 16 rows or more were used, excellent sensitivity and specificity values for the diagnosis of arterial mesenteric ischemia were able to be achieved [112].…”
Section: Arterial Occlusionmentioning
confidence: 96%
“…The severity of injury depends on etiology of ischemia, systemic blood pressure, collateral circulation flow, response of mesenteric vessels to autonomic stimulators, amounts of circulatory autonomic stimulators, regional hormonal factors, presence of cellular metabolites after reperfusion of the ischemic bowel, and duration of ischemia 2,7,11,12,17,23,24,25,26 Four pathologic factors have been described as the cause of acute mesenteric ischemia including: superior or inferior mesenteric artery emboli, thrombosis of these vessels, venous thrombosis, and non occlusive mesenteric ischemia 5,9,12,21 Emboli is the most common cause of AMI 1,14,15,25 Appropriate diagnosis of this disease depends on a high clinical suspicion particularly in elderly an patient who has history of cardiovascular disease 14,7,21,22 Early diagnosis and early intervention to ameliorate vascular obstruction are critical in patient's salvage 1,4,9,22,27 . Appropriate resuscitation of the patient and diagnostic studies and early surgical or non surgical intervention is the most effective approach to save the patient 1,3,9,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Основными инструметальными методами диагностики являются: ультразвуковое дуп лексное сканирование, спиральная компьютер ная томография (СКТ), магниторезонансная томография в режиме непрямой ангиографии (МРТ ангиография) и прямая ангиография [25,26,27]. Еще одним высокоинформатив ным, но, к сожалению, малодоступным в нашей стране методом диагностики СХАИ является эндоскопическое измерение напряжения PCO2 либо PO2 в слизистой оболочке желудка и ки шечника [28].…”
unclassified
“…Однако он не дает возможности су дить о характере коллатерального кровотока и о состоянии нижней брыжеечной артерии из за малого ее диаметра. Данное исследование яв ляется скрининговым методом для отбора больных на ангиографию [26]. Высокой информативностью также облада ют неинвазивные современные методики иссле дования сосудов -СКТ и МРТ ангиография.…”
unclassified
See 1 more Smart Citation